CITRA PEREMPUAN DALAM NOVEL YUSUF ZULAIKHA KARYA ABIDAH EL KHALIEQY - Anggaira, Aria Septi (Center of Gender Studies and Child of State Islamic Institute of Metro, 2020)
Gender inequalities has become an interesting topic for novelists to be their literary works. One of the novelists who like to discuss this topic is Abidah El Khaileqy. This was a literary research from Abidah El Khaileqy with a descriptive qualitative approach using content analysis methods. The purpose of this research was to examine the image of the main female character in Yusuf Zulaikha's novel related to the perspective of life and the struggle for women's lives. The data in this study were the results of the analysis of the novel Yusuf Zulaikha by Abidah El Khalieqy consisting of words, sentences, character descriptions, and dialogue between figures who describe and interpret the views of women and the life struggles of women. Based on the analysis, 72 data were obtained related to the views of life of women and the life struggles of women in the form of quotes. Zulaikha is imaged as a woman who is steadfast and patient in supporting life. Zulaikha is also imaged as a woman with a strong view and principle of life, with a winding journey of love, and with determination in the struggle to enjoy life. In addition, Zulaikhaa is also imaged for her struggle against stereotypes against women and her struggle against physical/ emotional violence.